Development of algorithm of time and space domain for chlorophyll-a (Chl-a) and total suspended sediment (TSS) at Teluk Lipat Terengganu Coastline / Fathinul Najib Ahmad Sa’ad - Ahmad Sa’ad, Fathinul Najib (2023)
Chlorophyll-a (Chl-a) and Total suspended sediment (TSS) is a water quality parameter that can be currently determined using remote sensing technology. Several algorithms that have been developed across different regions indicate that algorithms are highly regional dependent due to differences in the optical properties of suspended matter. However, the developed algorithms are highly regional dependence. In order to precisely estimate the TSS and Chl-a concentration, new algorithm need to develop. The objective of this study is to develop a regional Chl-a and TSS algorithms for Teluk Lipat, Malaysia by utilising Landsat 8 and in situ datasets. A first field trip was conducted in the study area on 28 March 2018, concurrent with the passing of Landsat 8. A total of 30 samples were collected during the trip. The samples were then analysed using an established lab method to determine Chl-a and TSS concentrations. The image acquired on 28 March 2018 was used. The images were the processed using Envi 5.1. The relationship between in situ TSS and Chl-a with remote sensing reflectance was identified using a regression analysis technique.